First report of Agaricus micromegatuus found in Northern Guinea Savanna of Nigeria, West Africa - DAUDA, WADZANI (Mushroom Research, 2020)
Agaricus is a general name of macrofungi of the family Agaricaceae. Mushrooms vary according to the species, strain, environment and growth conditions. A detail morphological description of Agaricus micromegatuus belonging to the order Agaricales was carried out. The taxon was described and identified using conventional keys. Morphological characters of the wild mushrooms were observed and their morphometrics were recorded thus: Presence of veil with ring, presence or absence of hollow stipe and bulbous base, close or free attached gills (lamellae) in the pileus, shapes and sizes, color and texture of pileus and stalk. Morphological studies revealed that Agaricus mushrooms exhibited hymenium with basidia and basidiospores. Spore prints were collected and spore characters were recorded. The morphology of Agaricus micromegatuus showed cap diameter of 4.0 – 10.0 cm. However, their basidiospores shapes were smooth and elliptical and measured 4.5-5.5×3.5-4.0µ with decurrent and parallel interwoven trama. This is the first report on Agaricus micromegatuus from Northern Guinea Savanna of Nigeria. The species has been deposited in the herbarium of the Department of Biological Sciences, Ahmadu Bello University, Zaria, Nigeria.